AROMA TERAPI LAVENDER SEBAGAI ALTERNATIF PENURUNAN STRES KERJA PERAWAT DI RUMAH SAKIT - Nelly; Tiara Ramadhanti, Elsa; Siregar, Tatiana; Kurniasih, Een (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Work stress can cause health problems to impact the quality of nurses' work. Intervention is needed to reduce work stress in order to avoid detrimental effects. The aim of this research is to determine the effect of giving lavender aromatherapy on lavender aromatherapy therapy by inhalation, where inhaling lavender essential oil has calming properties that can reduce stress, including work stress, work stress as a nurse. This research uses a Quasi Experiment research design with One Group Pre – Post Test Design. The population in this study were 20 nurses in the Isolation Room at a hospital in Jakarta. The sampling technique uses Consecutive sampling. The total sample was 20 respondents with minimum criteria of D3 Nursing. The data were analyzed using the Repeated Measures Anova Test, with the results that there was an effect of giving lavender aromatherapy with a P value of 0.00 (P value < 0.05 CI 95%) on the intervention. The research results also show that there is a difference in results between before and after the second, third and fourth interventions with a P value of 0.00 (P value < 0.05). This research is recommended for nurses as an alternative method for reducing work stress.